Hubungan Geomorfometri Dengan Bentuk Lahan Dan Penggunaan Lahan Sub-Sub Das Riam Kanan Kabupaten Banjar Kalimantan Selatan - zainal abidin; Nurlina Nurlina; Ichsan Ridwan (Jurnal Fisika FLUX, 2019)
ABSTRACT-  Identification  geogorphometric  of  the  "Topographic  Wetness  Index  and  Terrain Ruggedness Index" has been carried out in the Riam Kanan sub-watershed to determine the type and distribution and its relationship with landforms and land use. The material used in this study is imagery SRTM 30 m, Google Earth imagery. The research process begins with secondary data collection, the next process is the interpretation of image SRTM 30 m imagery in order to obtain landform  maps,  interpretations  of  Google  Earth  imagery  in  order  to  obtain  land  use  maps, correlate 30 m SRTM images through digital processes to classify the Terrain Ruggedness Index (TRI)  and  Topographic  Wetness  Index  (TWI).  The  final  process  is  data  analysis  by  overlaying landform maps, land use and TRI and TWI. The results of the research data have obtained an area of 116,650.03 ha out of 13 types of distribution of landforms dominated by structural mountains which  are  quite  extensive  with  38,200.08  ha  while  land  use  consists  of  8  types  of  distribution dominated  by  forest  areas  with  an  area  of  88,070.15  ha.  The  results  of  the  TWI  analysis  were dominated  by  class  1  (dry)  with  an  area  of  80,193.87  ha  while  TRI  was  dominated  by  class  3 (medium) with an area of 66,400.64 ha. Both TWI and TRI contained in landforms and land use are dominated by structural mountainous landforms which are quite insignificant and use of forest land. Keywords: Geomorphometry, LandForm, LandUse, Overlay.